If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x=-13+0.1/0.5
We move all terms to the left:
x-(-13+0.1/0.5)=0
We add all the numbers together, and all the variables
x-(0.1/0.5-13)=0
We get rid of parentheses
x+13-0.1/0.5=0
We multiply all the terms by the denominator
x*0.5-0.1+13*0.5=0
We add all the numbers together, and all the variables
x*0.5+6.4=0
Wy multiply elements
0.5x+6.4=0
We move all terms containing x to the left, all other terms to the right
0.5x=-6.4
x=-6.4/0.5
x=-12+0.4/0.5
| -9b+15=15-9b | | 14(12−8x)=23(6x) | | 4f=-24 | | 6-7(a=1)=-392-a0 | | 28.5=5x+12.5 | | 3x(x-7)(2x+7)=0 | | (-x)=9 | | 1”21x+4=21x+29 | | -6=15-2/3x | | -3(n-2)+6(n+3)=9-5(n-3)+8n) | | 8x+5-3x=2x+7 | | -17f+19f=2f | | 0.5(5-7t)=8-(4t+6) | | 1/2x+1/2x=1+x | | -7(x+7)=15 | | -9(6n-5)-3=-336 | | 13+19=-4(2x-8) | | 2x-17+8+2=x+20 | | -7x+10=-x+70 | | 2(5x-3)=3(3x-2)+x | | -(x)=9 | | U=-5u+6u | | 7x/4+48=13x/4 | | s11-s=24 | | x-5=-6x+58 | | 63=-1x | | -(-x)=-9 | | 7x/4+48=13x/44 | | -3=15-2/3x | | 2x+52=-x/6 | | 2=-8/b | | 18(x+12)=7 |